The strategies used to deal with emotion work in student paramedic practice - Angela Williams (Nurse Education in Practice, 2012)
Preregistration paramedic science students are quickly introduced to the reality of emergency paramedic practice (British Paramedic Association 2006) and are expected to manage both their own emotions and those of potentially distressed patients and relatives. Despite the evident importance of emotion work, there is a lack of research evidence on this phenomenon and none at all from the student perspective. A qualitative study, using semi-structured interviews was undertaken with eight second year paramedic science students to explore their perceptions and experiences of emotion work and the strategies used to deal with it. Thematic content analysis produced four themes, ‘getting on with the job’, ‘struggling with emotion’,’ talking it through’ and humour. This paper focuses on the strategies used to help deal with the emotional demands of practice. Participants emphasised the importance of talking it through and ‘off loading’ with friends, colleagues and partners. Going through the job with their mentor centred on the technical aspects of care and helped to reassure students that they had done their best. Humour was another useful strategy which also helped them to ‘off load’ and move on after difficult experiences. These findings highlight the importance of talking about experiences within available support systems and the role of the clinical mentor in facilitating debriefing and reflection. It is crucial that paramedic students are also made aware of the support services available to them to ensure their emotional needs are met.